APPLICATION OF TRISHEAR FAULT-PROPAGATION FOLDING TO ACTIVE REVERSE FAULTS: EXAMPLES FROM THE DALONG FAULT, GANSU PROVINCE, NW CHINA - Gold R.D.; Cowgill E.; Wang X.-F.; Chen X.-H. (My University, 2006)
Determining accurate fault slip rates at 1 ka to 1 Ma timescales requires well-constrained palinspastic reconstructions of dateable geomorphic and/or geologic markers. Although general kinematic models have been developed to simultaneously reconstruct both bedrock (e.g. bedding and fault attitudes) and neotectonic markers (e.g. strath terraces) along active strike-slip and thrust faults, it is not clear if these models can also account for deformation along steeply dipping (>45°) reverse faults. To address this problem, we have investigated the active, ~50° dipping, Dalong reverse fault system. This ~40-km-long fault system forms part of the Aksai restraining stepover along the active, left-slip Altyn Tagh Fault in northwestern China. Our geometric and kinematic analyses show that conventional fault-bend fold models cannot satisfy the steeply-dipping fault geometry we observe in the bedrock record. Likewise, standard fault-propagation fold models fail to match our measurements of a set of fluvial terraces. However, by expanding the trishear model of fault-propagation folding to track both bedrock and neotectonic markers, we are able to match both sets of records. In particular, we have developed trishear kinematic models for two sites (Liuchenzi and Qingyazi) using the numerical modeling program, Fault/Fold v.5.0. This work indicates that an important implication of active trishear fault-propagation folding is that terrace deformation extends for over 1 km on either side of the fault trace. Thus, to accurately measure the total magnitude of vertical separation between matching terraces in the hanging wall and footwall, terrace profiles across active reverse faults must extend 1-2 km on either side of this zone of deformation. © 2006 Elsevier Ltd. All rights reseved.
Keywords: FAULT-PROPAGATION FOLDS; NEOTECTONICS; RESTRAINING BENDS; REVERSE FAULTS; TRANSECT DATA; TRISHEAR